On the possibility of using information entropy as a quantitative description of porous media structural characteristics - Yelshin, Alexander (1996)
This paper deals with possibility of information entropy usage for porous media structure characteristics description. The paper presents the results of preliminary investigation of the possibility using information entropy parameter for porous media. The first approach of the method presented in the paper confirmed the possibility to get the join characteristic of porous media. The method may give a new point of view on the problem of porous media modelling. The examples of entropy calculation for distributions of pore by size and length as well as for multi-layers porous media joint entropy are given.